THE EFFECT OF MORINGA OLEIFERA LEAVES ON CHANGE IN BLOOD PROFILE IN POSTPARTUM MOTHERS - Arum Estiyani; Ari Suwondo; Sri Rahayu; Suharyo Hadisaputro; Melyana Nurul Widyawati; Kun Aristiati Susiloretni (Belitung Raya Foundation, Indonesia, 2017)
Background: Postpartum anemia among mothers is a health problem in Indonesia. Consuming moringa oleifera is assumed as one of the efforts to deal with anemia. However, lack of the study conducted in the working in the working area of Health Center of Tlogosari Wetan, Indonesia. Objective: This study was conducted to examine the effect of moringa oleifera on blood profile in postpartum mothers. Methods: The study was quasi-experimental study with pretest posttest control group design. The sample in this study were all postpartum mothers in the working area of the Health Center of Tlogosari Wetan. It was 30 respondents selected by purposive sampling, divided into intervention group (15 respondents) who received moringa leaf capsule and iron tablet, and control group (15 respondents) were given iron tablet. Data were analyzed using Independent t-test. Results: Findings showed a significant difference in the mean of hemoglobin level (intervention group 11.9467; control group 11.0600), hematocrit (intervention group 38.3867; control group 33.8133), thrombocyte (intervention group 3.02536; control group 2.35805), and erythrocyte (intervention group 4.30137; control group 3.78206) with p-value < 0.05. Conclusion: there was a significant effect of moringa oleifera on changes in blood profile (hemoglobin, hematocrit, erythrocyte, thrombocyte) in postpartum mothers in the working area of the Health Center of Tlogosari Wetan. Thus, it is suggested that moringa leaves could be used to prevent anemia in postpartum mothers.